"Doc in the Box": The impact of an emergency department move on interprofessional collaboration, patient care, and clinician job satisfaction. (March 2023) - Plusch, Jamie; Jane Muir, K.
Highlights: Understudied in the health care literature, hospital renovation and expansion projects help emergency departments accommodate rising patient volumes. Few studies evaluate the impact of emergency department physical space reconfigurations on interprofessional collaboration, patient care delivery, and clinician job satisfaction. Using qualitative descriptive methods, we found that changes in emergency department physical space resulted in siloed interprofessional collaboration, patient surveillance challenges, but improvements to privacy and aesthetic-aspects of the work environment. On a global scale, emergency departments represent the first entrance to hospitals and acute care for patients. Understanding the impacts of hospital physical reconfiguration projects is important for clinician team collaboration, job satisfaction, and in turn patient quality care. Abstract: Objective: Health care organizations undergo unit space reconfiguration (e.g., expansion) projects in order to accommodate rising patient volumes with limited health care space. The purpose of this study was to describe the impact of an emergency department physical space move on clinician-perceived interprofessional collaboration, patient care delivery, and clinician job satisfaction. Method: A secondary qualitative, descriptive data analysis of 39 in-depth interviews from an ethnography was conducted from August 2019 to February 2021 at an academic medical center emergency department with nurses, physicians, and patient care technicians in the Southeastern United States. The Social Ecological Model was a conceptual guide for the analysis. Results: Three study themes, "It's like an old dive bar", "spatial blind spot", and "privacy and aesthetic work environment" emerged from the 39 interviews. Clinicians perceived that the move from a centralized to decentralized work space impacted interprofessional collaboration through divided clinician work spaces. Increased square footage in the new emergency department was beneficial for patient satisfaction but contributed to difficulty monitoring patients for care escalation. However, increased space and individualized patient rooms increased perceived clinician job satisfaction. Conclusion: Space reconfiguration projects in health care can have positive implications for patient care, but may result in inefficiencies to the health care team and patient care that must be considered. Study findings inform health care work environment renovation projects on an international level.